1979
DOI: 10.1136/sti.55.6.408
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of rectal and pharyngeal infection in women with gonorrhoea in Sheffield.

Abstract: SUMMARY The prevalence of gonococcal infection of the rectum and pharynx in 239 consecutive women with gonorrhoea presenting as named contacts was 47% and 10%7o respectively. In 2%'o of all patients the rectum and pharynx were each the sole sites of infection. Treatment failure occurred in three patients given a single dose of aqueous procaine penicillin 2 4 megaunits intramuscularly, two of whom had rectal infections; no treatment failures occurred in patients with pharyngeal infections.The incidence of recta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…12 The prevalence of concurrent rectal gonorrhea increases with the duration of cervical infection, because time increases the chance of perineal contamination. 19 Thus, one explanation may be that adolescent women seen in an STD clinic have less access to health care and a longer duration of cervical gonorrhea infections, leading to a higher prevalence of rectal infections from perineal contamination rather than from anal sex.…”
Section: Discussionmentioning
confidence: 99%
“…12 The prevalence of concurrent rectal gonorrhea increases with the duration of cervical infection, because time increases the chance of perineal contamination. 19 Thus, one explanation may be that adolescent women seen in an STD clinic have less access to health care and a longer duration of cervical gonorrhea infections, leading to a higher prevalence of rectal infections from perineal contamination rather than from anal sex.…”
Section: Discussionmentioning
confidence: 99%
“…Our results along with published studies suggest that if vaginal screening alone is used, missed infection ranges from 18–40% for GC 5,16,17,22 and 6–25% for CT. 4,5,16,17,19 Although there was past debate about whether the rectum was truly infected in women having STIs, 23 recent reports document that the rectum can serve as a reservoir. 24,25 Gratix, et al 18 reported that when CT testing was expanded to include evaluation of rectal swabs, case detection for CT increased by 44%, leading them to support universal screening of women attending STI clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Second, there is the possibility that false positive rectal GC/CT results may be due to cross contamination with urogenital secretions during sample collection, especially for samples tested by NAAT and if rectal samples are obtained without the use of a proctoscope. 6,10,16,[29][30][31] The risk of cross contamination is a challenge for all studies that characterize rectal GC/CT infection in women. Nevertheless, in our study, 14% of women with rectal GC did not have urogenital GC and 14% of women with rectal CT did not have urogenital CT. We believe that cross contamination cannot be wholly responsible for the high prevalence of rectal infections identified in this study.…”
Section: Discussionmentioning
confidence: 99%